Nursing assistance for people with Systemic Arterial Hypertension: an integrative review (Research, Society and Development, 2021)
Systemic arterial hypertension (SAH) represents clinical condition multifactorial characterized by in the blood pressure ≥ 140 and/ or 90 mmHg. The high number of cases and the low control rates of the pathology configure it as an ascendant phenomenon, constituting a serious Public Health problem in the country. The objective was to analyze nursing care for people with hypertension through an integrative review of the scientific literature. An integrative literature review was carried out by systematically searching for articles in journals indexed in the LILACS and SciELO databases, published in the last 5 years. The present search was carried out in the period February to March 2021. We used 12 articles published in Brazil and/or by Brazilians.The content analysis technique used was related through the exclusion and inclusion criteria of the study objectives. Based on the systematization of this built knowledge it was evident that nursing care to the patient with systemic arterial hypertension is provided through healthiness education. As well as, obtaining an accurate diagnosis for analysis of adherence to treatment, medicated  or non- medicated. Furthermore, it is important to know that all this integrality of patient care is always done with a focus on socio-emotional well-being, considering that dealing with the chronicity of hypertension becomes somewhat complex, since the treatment lasts a lifetime.